Biocompatible Tissue Scaffold Compliance Promotes Salivary Gland Morphogenesis and Differentiation - Peters, Sarah B. (Mary Ann Liebert, Inc., 2014)
Substrate compliance is reported to alter cell phenotype, but little is known about the effects of compliance on cell development within the context of a complex tissue. In this study, we used 0.48 and 19.66 kPa polyacrylamide gels to test the effects of the substrate modulus on submandibular salivary gland development in culture and found a significant decrease in branching morphogenesis in explants grown on the stiff 19.66 kPa gels relative to those grown on the more physiologically compliant 0.48 kPa gels. While proliferation and apoptosis were not affected by the substrate modulus, tissue architecture and epithelial acinar cell differentiation were profoundly perturbed by aberrant, high stiffness. The glands cultured on 0.48 kPa gels were similar to developing glands in morphology and expression of the differentiation markers smooth muscle alpha-actin (SM α-actin) in developing myoepithelial cells and aquaporin 5 (AQP5) in proacinar cells. At 19.66 kPa, however, tissue morphology and the expression and distribution of SM α-actin and AQP5 were disrupted. Significantly, aberrant gland development at 19.66 kPa could be rescued by both mechanical and chemical stimuli. Transfer of glands from 19.66 to 0.48 kPa gels resulted in substantial recovery of acinar structure and differentiation, and addition of exogenous transforming growth factor beta 1 at 19.66 kPa resulted in a partial rescue of morphology and differentiation within the proacinar buds. These results indicate that environmental compliance is critical for organogenesis, and suggest that both mechanical and chemical stimuli can be exploited to promote organ development in the contexts of tissue engineering and organ regeneration.